Brain and breast cancer cells with pten loss of function reveal enhanced durotaxis and rhob dependent amoeboid migration utilizing 3d scaffolds and aligned microfiber tracts - Wieland, Annalena; Strissel, Pamela; Schorle, Hannah; Bakirci, Ezgi; Janzen, Dieter; Beckmann, Matthias; Eckstein, Markus; Dalton, Paul D.; Strick, Reiner (Cancers, 2021)
Background: Glioblastoma multiforme (GBM) and metastatic triple-negative breast cancer (TNBC) with PTEN mutations often lead to brain dissemination with poor patient outcome, thus new therapeutic targets are needed. To understand signaling, controlling the dynamics and mechanics of brain tumor cell migration, we implemented GBM and TNBC cell lines and designed 3D aligned microfibers and scaffolds mimicking brain structures. Methods: 3D microfibers and scaffolds were printed using melt electrowriting. GBM and TNBC cell lines with opposing PTEN genotypes were analyzed with RHO-ROCK-PTEN inhibitors and PTEN rescue using live-cell imaging. RNA-sequencing and qPCR of tumor cells in 3D with microfibers were performed, while scanning electron microscopy and confocal microscopy addressed cell morphology. Results: In contrast to the PTEN wildtype, GBM and TNBC cells with PTEN loss of function yielded enhanced durotaxis, topotaxis, adhesion, amoeboid migration on 3D microfibers and significant high RHOB expression. Functional studies concerning RHOB-ROCK-PTEN signaling confirmed the essential role for the above cellular processes. Conclusions: This study demonstrates a significant role of the PTEN genotype and RHOB expression for durotaxis, adhesion and migration dependent on 3D. GBM and TNBC cells with PTEN loss of function have an affinity for stiff brain structures promoting metastasis. 3D microfibers represent an important tool to model brain metastasizing tumor cells, where RHO-inhibitors could play an essential role for improved therapy.
CRIS-Team Scopus Importer:2021-10-29
Keywords: 3D microfiber; 3D tumor model; Amoeboid cell migration; Brain cancer; Breast cancer; Durotaxis; PTEN; RHO; ROCK; Topotaxis